Help the children of Spain (leaflet) (1937)
039-0069-001 NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF 53, Marsham Street, London, S.W.1 Chairman: The Duchess of Atholl, M.P Hon. Treasurer: Wilfrid Roberts, M.P. PLEASE HELP US TO HELP THE CHILDREN OF SPAIN THANK YOU. 292/946/39/69